Set-Point Tracking Analysis of Various Controllers Designed for Orthonormal Basis Filter Process Model - Yadav, Pratibha; Sundriyal, Nitin (Journal of Graphic Era University, 2023)
<span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*305.33px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.914317);" role="presentation">Over the past 50 years PID controllers <span dir="ltr" style="left: calc(var(–scale-factor)*229.37px); top: calc(var(–scale-factor)*305.33px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.907449);" role="presentation">are used in controlling the linear feedback control system processes. <span dir="ltr" style="left: calc(var(–scale-factor)*506.86px); top: calc(var(–scale-factor)*305.33px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.905504);" role="presentation">Due <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*318.53px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.910707);" role="presentation">to simplicity and reduced number of parameters to b<span dir="ltr" style="left: calc(var(–scale-factor)*281.69px); top: calc(var(–scale-factor)*318.53px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.89989);" role="presentation">e tuned, PID controllers are used in process industries. <span dir="ltr" style="left: calc(var(–scale-factor)*502.30px); top: calc(var(–scale-factor)*318.53px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.968995);" role="presentation">Time <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*331.73px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.962131);" role="presentation">delay models are mostly considered for tuning PID controllers. <span dir="ltr" style="left: calc(var(–scale-factor)*340.15px); top: calc(var(–scale-factor)*331.73px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.990276);" role="presentation">An <span dir="ltr" style="left: calc(var(–scale-factor)*356.23px); top: calc(var(–scale-factor)*331.73px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.972654);" role="presentation">Orthonormal Basis Filter (<span dir="ltr" style="left: calc(var(–scale-factor)*466.78px); top: calc(var(–scale-factor)*331.73px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.950263);" role="presentation">OBF) <span dir="ltr" style="left: calc(var(–scale-factor)*493.54px); top: calc(var(–scale-factor)*331.73px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.860078);" role="presentation">process <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*345.05px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.911871);" role="presentation">model, which can be represented as a <span dir="ltr" style="left: calc(var(–scale-factor)*229.13px); top: calc(var(–scale-factor)*345.05px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.924947);" role="presentation">Second Order Plus Dead Time (<span dir="ltr" style="left: calc(var(–scale-factor)*361.03px); top: calc(var(–scale-factor)*345.05px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.921953);" role="presentation">SOPDT) <span dir="ltr" style="left: calc(var(–scale-factor)*399.55px); top: calc(var(–scale-factor)*345.05px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.914499);" role="presentation">model <span dir="ltr" style="left: calc(var(–scale-factor)*427.63px); top: calc(var(–scale-factor)*345.05px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.924342);" role="presentation">is selected and delay in <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*358.25px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.909915);" role="presentation">the process model is approximated using <span dir="ltr" style="left: calc(var(–scale-factor)*239.81px); top: calc(var(–scale-factor)*358.25px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.00462);" role="presentation">Taylor <span dir="ltr" style="left: calc(var(–scale-factor)*269.45px); top: calc(var(–scale-factor)*358.25px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.886263);" role="presentation">series. C<span dir="ltr" style="left: calc(var(–scale-factor)*304.25px); top: calc(var(–scale-factor)*358.25px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.958086);" role="presentation">ontroller <span dir="ltr" style="left: calc(var(–scale-factor)*341.71px); top: calc(var(–scale-factor)*358.25px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.923967);" role="presentation">is <span dir="ltr" style="left: calc(var(–scale-factor)*351.19px); top: calc(var(–scale-factor)*358.25px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.913606);" role="presentation">design based on diffe<span dir="ltr" style="left: calc(var(–scale-factor)*437.71px); top: calc(var(–scale-factor)*358.25px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.942921);" role="presentation">rent controller tuning <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*371.45px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.884162);" role="presentation">techniques<span dir="ltr" style="left: calc(var(–scale-factor)*114.62px); top: calc(var(–scale-factor)*371.45px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.03408);" role="presentation">. On <span dir="ltr" style="left: calc(var(–scale-factor)*138.86px); top: calc(var(–scale-factor)*371.45px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.00276);" role="presentation">the basis of the comparison of t<span dir="ltr" style="left: calc(var(–scale-factor)*277.85px); top: calc(var(–scale-factor)*371.45px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.928108);" role="presentation">he set-<span dir="ltr" style="left: calc(var(–scale-factor)*306.41px); top: calc(var(–scale-factor)*371.45px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.997937);" role="presentation">point tracking capability of the controllers <span dir="ltr" style="left: calc(var(–scale-factor)*491.02px); top: calc(var(–scale-factor)*371.45px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.975618);" role="presentation">for step <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*384.65px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.850902);" role="presentation">response, <span dir="ltr" style="left: calc(var(–scale-factor)*111.98px); top: calc(var(–scale-factor)*384.65px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.901835);" role="presentation">best controller tuning technique is examined for the selected process.